2015
DOI: 10.3906/bot-1410-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cobalt nanoparticles on artemisinin production and gene expression in Artemisia annua

Abstract: The low artemisinin content in Artemisia has caused this compound to be expensive among medicines. Several attempts have been made to increase its production by altering the expression of different genes. However, no approach has been cost-effective. In this study, the expression levels of SQS and DBR2 genes were quantified by qRT-PCR, and artemisinin content was measured by HPLC in Artemisia annua cell suspension culture under nano cobalt particles elicitation. For this purpose, nano cobalt particles were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Yang et al [49] revealed that overexpression of pmt and h6h genes in A. belladonna L. caused a huge increase (11-and 24fold, respectively) in hyoscyamine content in elicited hairy roots compared to control and native roots. Similarly, cobalt and zinc nanoparticles have been shown to increase the expression of genes associated with the artemisinin biosynthetic pathway and have been proposed as elicitors to enhance artemisinin production [51]. In this study, the highest h6h gene expression was observed when hairy roots were treated with 100 mg/L ZnO after 48 h, being 4.2-fold higher than in the nonelicited hairy roots.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Yang et al [49] revealed that overexpression of pmt and h6h genes in A. belladonna L. caused a huge increase (11-and 24fold, respectively) in hyoscyamine content in elicited hairy roots compared to control and native roots. Similarly, cobalt and zinc nanoparticles have been shown to increase the expression of genes associated with the artemisinin biosynthetic pathway and have been proposed as elicitors to enhance artemisinin production [51]. In this study, the highest h6h gene expression was observed when hairy roots were treated with 100 mg/L ZnO after 48 h, being 4.2-fold higher than in the nonelicited hairy roots.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, the highest h6h gene expression was observed when hairy roots were treated with 100 mg/L ZnO after 48 h, being 4.2-fold higher than in the nonelicited hairy roots. Similarly, cobalt and zinc nanoparticles have been shown to increase the expression of genes associated with the artemisinin biosynthetic pathway and have been proposed as elicitors to enhance artemisinin production [51].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the highest artemisinin content (2.2fold increase over the control) was obtained in cell suspension cultures of A. annua 24 h aer treatment with 5 mg L À1 Co NPs. 96 The authors concluded that the Co NP treatment increased the artemisinin content as a result of downregulation of the SQS and DBR2 genes. Shakeran et al 97 investigated the effects of biotic (Bacillus cereus and Staphylococcus aureus) and abiotic (AgNO 3 and Ag NPs) elicitors on atropine production in hairy root cultures of Datura metel.…”
Section: Nanomaterials Enhancement Of Secondary Metabolitesmentioning
confidence: 99%
“…The unique properties of nanoparticles as compared with their large-particle counterparts (29), may introduce a new button for fine tuning stress treatment. Cobalt nanoparticles were employed to enhance artemisinin synthesis in Artemisia annua suspension cultures (30).…”
Section: Introductionmentioning
confidence: 99%